2019
DOI: 10.1186/s12887-019-1878-8
|View full text |Cite
|
Sign up to set email alerts
|

Association of adverse childhood experiences and neurodevelopmental disorders in people with fetal alcohol spectrum disorders (FASD) and non-FASD controls

Abstract: BackgroundFetal alcohol spectrum disorder (FASD) is a highly prevalent lifelong disorder with high rates of comorbid neurodevelopmental disorders. Individuals with FASD are often exposed to abuse, neglect and foster home placements which have uncertain effects on the lifelong course of FASD. In this study we compare the prevalence of adverse childhood events (ACEs) and neurodevelopmental disorders in subjects with fetal alcohol spectrum disorders (FASD) and non-FASD controls.MethodsA cross-sectional chart revi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
71
0
3

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 78 publications
(79 citation statements)
references
References 41 publications
5
71
0
3
Order By: Relevance
“…The results of this study are in line with previous findings showing a strong association between traumatic experiences ( Henry et al, 2007 ; Kambeitz et al, 2019 ; Koponen, 2006 ; Koponen et al, 2009 ; 2013 ; Lambert & Bauer, 2012 ; Price et al, 2017 ), residential care ( Sarkola et al, 2011 ; Fagerlund et al, 2011 ) and an increased risk of mental health problems among children and adolescents with PAE and PDE. Numerous studies carried out among the general population have also revealed the relationship between socioeconomic inequalities, multiple ACEs and high levels of mental health problems ( Hughes et al, 2017 ; Paananen et al, 2013 ; Reiss, 2013 ; Ristikari et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…The results of this study are in line with previous findings showing a strong association between traumatic experiences ( Henry et al, 2007 ; Kambeitz et al, 2019 ; Koponen, 2006 ; Koponen et al, 2009 ; 2013 ; Lambert & Bauer, 2012 ; Price et al, 2017 ), residential care ( Sarkola et al, 2011 ; Fagerlund et al, 2011 ) and an increased risk of mental health problems among children and adolescents with PAE and PDE. Numerous studies carried out among the general population have also revealed the relationship between socioeconomic inequalities, multiple ACEs and high levels of mental health problems ( Hughes et al, 2017 ; Paananen et al, 2013 ; Reiss, 2013 ; Ristikari et al, 2018 ).…”
Section: Discussionsupporting
confidence: 92%
“…This finding also remained significant when groups were examined by age. The finding that abuse was higher among individuals in care may be explained by abuse being a common reason for involvement with the child welfare system (Badry, 2009;Kambeitz et al, 2019 among child welfare (Mukherjee, Cook, Norgate, & Price, 2019). The results of this study support previous research that speaks to the high rate of abuse experienced by children and youth within the child welfare system (Mukherjee et al, 2019) and points to the need for further research that explores the protective factors for children with FASD in care who may have a history of abuse.…”
Section: Sexual and Physical Abusesupporting
confidence: 81%
“…This finding also remained significant when groups were examined by age. The finding that abuse was higher among individuals in care may be explained by abuse being a common reason for involvement with the child welfare system (Badry, 2009; Kambeitz et al, 2019). A concerning finding was that when considering all living situations of individuals in our sample, over 30% experienced abuse.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Adverse childhood experiences (ACEs), such as trauma, need to be understood in the context of preventing alcohol consumption during pregnancy and FASD. Women with ACEs are more likely to consume alcohol during pregnancy, and individuals with FASD are more likely to have ACEs, which contributes to the development of comorbid disorders in FASD (Kambeitz et al, 2019; Weyrauch et al, 2017). Understanding the important role of FASD as a predisposing risk marker for ACEs could reduce the large economic burden placed on service systems (Kambeitz et al, 2019), could improve outcomes for diagnosed individuals, and could possibly prevent FASD familial recurrence.…”
Section: Preventionmentioning
confidence: 99%